Author Correction: Selective Priming of Tumor Blood Vessels by Radiation Therapy Enhances Nanodrug Delivery - Kunjachan, Sijumon; Kotb, Shady; Pola, Robert; Pechar, Michal; Kumar, Rajiv; Singh, Bijay; Gremse, Felix; Taleeli, Reza; Trichard, Florian; Motto-Ros, Vincent; Sancey, Lucie; Detappe, Alexandre; et al. (Scientific reports, 2020)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.